Implementasi dan Pengaruh Kerangka Kerja TPACK dalam Pendidikan Matematika: Sebuah Tinjauan Literatur Sistematis - Djatnika, Raya; Nurjanah, Nurjanah (Papanda, 2026)
The integration of technology in mathematics education is often hindered by users' lack of technological proficiency or the misalignment between technology use and mathematical content. This study aims to evaluate the implementation and effectiveness of the Technological Pedagogical Content Knowledge (TPACK) framework on student learning outcomes. Using a Systematic Literature Review (SLR) method with the PRISMA protocol. Through the identification, screening, and eligibility assessment phases, this study selected 14 articles from the Scopus database published between 2015 and 2025. The results indicate that TPACK implementation is most dominant in subject domains with high levels of abstraction, such as Calculus and Geometry. Dynamic visualization technologies, particularly GeoGebra, and Game-Based Learning strategies are the most frequently used interventions. The findings confirm that TPACK-based learning consistently yields a significant positive impact on academic achievement, conceptual understanding, critical thinking skills, and student engagement. This study concludes that the success of technology integration depends not on the sophistication of the tools, but on the teacher's ability to design student-centered learning with technology serving as a cognitive bridge.